2019
DOI: 10.1111/jcmm.14836
|View full text |Cite
|
Sign up to set email alerts
|

LMO1 polymorphisms and the risk of neuroblastoma: Assessment of meta‐analysis of case‐control studies

Abstract: Neuroblastoma (NB), a neuroendocrine tumour, is one of the most prevalent cancers in children. The link between LMO1 polymorphisms and NB has been investigated by several groups, rendering inconclusive results. Here, with this comprehensive systematic review and up‐to‐date meta‐analysis, we aim to distinctively elucidate the possible correlation between LMO1 polymorphisms and NB susceptibility. Eligible studies were systematically researched and identified using PubMed, Web of Science and Scopus databases up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Interestingly, other studies involving rs204938 did not observe this association in either the Chinese or African American populations [60,62–65] . A recent meta-analysis performed by Hashemi et al [68] in 2020 confirmed most of the results on LMO1 SNPs from previous studies. They reported that the LMO1 polymorphisms rs110419 A>G, rs4758051 G>A, rs10840002 A>G, rs2168101 G>T, and rs204938 C>T were associated with decreased susceptibility to neuroblastoma.…”
Section: Lmo1 and Neuroblastomamentioning
confidence: 71%
“…Interestingly, other studies involving rs204938 did not observe this association in either the Chinese or African American populations [60,62–65] . A recent meta-analysis performed by Hashemi et al [68] in 2020 confirmed most of the results on LMO1 SNPs from previous studies. They reported that the LMO1 polymorphisms rs110419 A>G, rs4758051 G>A, rs10840002 A>G, rs2168101 G>T, and rs204938 C>T were associated with decreased susceptibility to neuroblastoma.…”
Section: Lmo1 and Neuroblastomamentioning
confidence: 71%
“…This discovery was opposite to a meta-analysis publication that assessed the association between LMO1 gene polymorphism and neuroblastoma risk. In that meta-analysis, the researcher found that the rs2168101 TT polymorphism was more likely to reduce the risk of neuroblastoma than the rs2168101 GT/GG polymorphisms, with an OR of 0.48 in the recessive model (TT vs. GT + GG: OR = 0.48, 95% CI = 0.31–0.75, P = 0.001) [ 41 ]. The obvious differences were mainly attributed to the following reasons: the relatively small size of subject populations, selection bias for participants, chance of the experiments, etc.…”
Section: Discussionmentioning
confidence: 99%
“…LMO1 functions as a neuroblastoma oncogene and is implicated as an oncogene in colorectal and lung cancer. 37,38 Proteins of the matrix metalloproteinase (MMP) family are involved in the breakdown of the extracellular matrix in normal physiological processes, such as embryonic development, reproduction, and tissue remodeling. Additionally, they are involved in disease processes such as arthritis and metastasis and have been reported as biomarkers of various cancers.…”
Section: Scna In Post-treatment Mrtmentioning
confidence: 99%